Design and analysis of depth cues on depth perception in interactive mixed reality simulation systems. Issue 2 (12th August 2021) - Li, Hengwei; Wang, Wei; Ma, Weiwei; Zhang, Gangsheng; Wang, Qingli; Qu, Jue
Abstract: Implementing an interactive mixed reality simulation system is an economical and risk‐free method for skill training. However, research to enhance the accuracy of mixed reality simulation has always been a challenge. One of the key indicators of a simulation's accuracy is the user's depth perception. Adding depth cues to the simulation scene can effectively increase the accuracy of depth perception. Therefore, in this study, we designed five depth cues to find the one most beneficial for depth perception: (1) depth bar, (2) location ball, (3) fixed window, (4) 3D wireframe, and (5) movable silhouettes. These depth cues were tested using an experimental system with two sets of experimental settings. The first experiment compared the five depth cues at five different viewing distances and showed that the movable silhouettes benefited depth perception accuracy the most. The second experiment compared depth perception accuracies among three different horizontal tilt settings, showing that depth perception accuracy is dependent on the horizontal tilt. Furthermore, different depth perception accuracies were obtained with and without depth cues, proving that the effects from the horizontal tilts were independent of depth cues. The results of these studies provide references for designing interactive mixed reality simulation systems. Abstract :